2019
DOI: 10.1038/s41598-018-37654-9
|View full text |Cite
|
Sign up to set email alerts
|

The word order of languages predicts native speakers’ working memory

Abstract: The relationship between language and thought is controversial. One hypothesis is that language fosters habits of processing information that are retained even in non-linguistic domains. In left-branching (LB) languages, modifiers usually precede the head, and real-time sentence comprehension may more heavily rely on retaining initial information in working memory. Here we presented a battery of working memory and short-term memory tasks to adult native speakers of four LB and four right-branching (RB) languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 107 publications
2
27
0
Order By: Relevance
“…First, we aimed to design the naturalistic utterance recall measure such that a similar test could easily (either automatically or with minimal researcher input) be created for other languages. Given studies suggesting that working memory abilities are affected by the nature of individual languages (Amici et al., 2019; MacDonald & Christiansen, 2002), including in L2 contexts (Van den Noort, Bosch, & Hugdahl, 2006), we administered recall tasks in both L2 (Spanish) and L1 (English). We therefore expected that Spanish L2 recall would be a better predictor of proficiency (measured via our translation test) than English L1 recall.…”
Section: Methodsmentioning
confidence: 99%
“…First, we aimed to design the naturalistic utterance recall measure such that a similar test could easily (either automatically or with minimal researcher input) be created for other languages. Given studies suggesting that working memory abilities are affected by the nature of individual languages (Amici et al., 2019; MacDonald & Christiansen, 2002), including in L2 contexts (Van den Noort, Bosch, & Hugdahl, 2006), we administered recall tasks in both L2 (Spanish) and L1 (English). We therefore expected that Spanish L2 recall would be a better predictor of proficiency (measured via our translation test) than English L1 recall.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, concerning the advantage in terms of working memory, some studies showed that different syntactic structures could induce some particularities in terms of the way we maintain information. For example, Amici et al (2019) showed that the syntax and word order of a language predicts the way we remember verbal and non-verbal stimuli in working memory tasks. In their study, a series of stimuli were presented to participants who spoke either a language with a head-final syntactic structure (e.g., Japanese, Korean.…”
Section: The Linguistic Characteristics Of the Languages At Stakementioning
confidence: 99%
“…Likewise, computational modeling, experimental work with human learners, and language emergence in certain cultural contexts (like the homesigns developed by isolated deaf communities) have shown that core properties of language, such as duality of pattern or compositionality, can emerge by iterated learning and cultural transmission (Sandler et al, 2005;Tamariz and Kirby, 2016) and that the same cognitive and biological biases can result in different language features in different cultural environments (Thompson et al, 2016). Increasingly, however, evidence suggests that language structure also impacts on basic cognitive abilities, such as effects of word order on working memory (Amici et al, 2019). As a consequence, language features, language learning, and cognitive architecture comprise a reinforcing feedback loop (Deacon, 2003;Clarke and Heyes, 2017), wherein genetic changes occurred to accommodate language-specific cognition (Jablonka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%